Clinical Implications of Fetal Heart Rate Interpretation Based on Underlying Physiology. Issue 2 (March 2020) - O'Brien-Abel, Nancy
Abstract : Abstract: Understanding the physiology of fetal oxygenation and various influences on fetal heart rate control supports nurses, midwives, and physicians in interpreting and managing electronic fetal heart rate tracings during labor and birth. Maternal oxygenation, placental circulation and exchange, umbilical blood flow and fetal circulation affect fetal oxygenation, which is reflected in observed fetal heart rate patterns. Fetal heart control is further influenced by the central and autonomic nervous systems, baroreceptors, chemoreceptors, humoral factors, sleep–wake patterns, breathing movements, medications, painful stimuli, sound and vibrations, and temperature. Knowledge of the physiologic basis for fetal heart rate pattern characteristics guides interventions to improve fetal oxygenation when indicated. A review and update on clinical implications of fetal heart rate pattern interpretation based on underlying physiology is presented. Abstract : Understanding the physiology of fetal oxygenation and various influences on the fetal heart rate supports nurses, midwives, and physicians in interpreting and managing electronic fetal heart rate tracings during labor and birth. A review and update on clinical implications of fetal heart rate pattern interpretation based on underlying physiology is presented.